The road traffic injury treatment network in mainland China - Zheng-guo Wang (422568) (2015)
The issue of road traffic safety in mainland China is particularly serious. The total number of vehicles is growing rapidly (e.g. 60 million in 2000 vs. 240 million in 2012); meanwhile the number of road traffic accidents and associated casualties still remains high and shows no signs of meaningful decline. It is reported road traffic causalities in China ranks highest in the world, with an annual death toll exceeding 100,000 and an average daily death toll of 300 [Yue, Liu & Cai, 2004]. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.104